Costs of publicly provided maternity services in Rosario, Argentina - Borghi Josephine; Bastus Silvia; Belizan María; Carroli Guillermo; Hutton Guy; Fox-Rushby Julia (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: This study estimates the costs of maternal health services in Rosario, Argentina. MATERIAL AND METHODS: The provider costs (US$ 1999) of antenatal care, a normal vaginal delivery and a caesarean section, were evaluated retrospectively in two municipal hospitals. The cost of an antenatal visit was evaluated in two health centres and the patient costs associated with the visit were evaluated in a hospital and a health centre. RESULTS: The average cost per hospital day is $114.62. The average cost of a caesarean section ($525.57) is five times greater than that of a normal vaginal delivery ($105.61). A normal delivery costs less at the general hospital and a c-section less at the maternity hospital. The average cost of an antenatal visit is $31.10. The provider cost is lower at the health centre than at the hospital. Personnel accounted for 72-94% of the total cost and drugs and medical supplies between 4-26%. On average, an antenatal visit costs women $4.70. Direct costs are minimal compared to indirect costs of travel and waiting time. CONCLUSIONS: These results suggest the potential for increasing the efficiency of resource use by promoting antenatal care visits at the primary level. Women could also benefit from reduced travel and waiting time. Similar benefits could accrue to the provider by encouraging normal delivery at general hospitals, and complicated deliveries at specialised maternity hospitals.